"Smoking and Bone Fragility: An Incidence Study on Osteoporosis Among Smokers”. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Osteoporosis is a metabolic bone condition characterized by progressive reduction in bone strength due to decreased bone mineral density (BMD). Tobacco consumption is considered a significant behavioral risk factor that interferes with bone remodeling by affecting osteoblastic activity, mineral balance, and endocrine function. While osteoporosis is often associated with aging, early bone changes related to tobacco exposure may occur in young adults.Aim: To assess the incidence of osteoporosis among adult smokers and to compare bone mineral density between smokers, smokeless tobacco users, and individuals without tobacco habits.Materials and Methods: A total of 90 subjects aged 20–45 years were included in this observational study and categorized into three equal groups: smokers, smokeless tobacco users, and non-users. Bone mineral density was evaluated at the calcaneum using a portable SONOST 2000 peripheral DEXA system. Based on T-score values, participants were classified as normal, osteopenic, or osteoporotic.Statistical analysis was carried out using SPSS version 21.0. Differences in mean T-scores were analyzed using one-way ANOVA, while associations between tobacco exposure and BMD status were examined using the Chi-square test. Correlation analysis was performed to determine the relationship between smoking intensity, duration, and T-score values. A p-value less than 0.05 was considered statistically significant.Results: Individuals with a smoking habit demonstrated lower mean T-scores compared to smokeless tobacco users and non-users. Osteoporosis was more frequently identified among smokers, whereas most non-users exhibited normal BMD values. Greater duration and frequency of smoking were associated with progressively lower T-scores.Conclusion: Tobacco use, particularly smoking, is strongly associated with reduction in bone mineral density. Preventive measures, including early screening and tobacco cessation counseling, are essential to minimize long-term skeletal complications.